Multilingual Representation In The Linguistic Landscape Of Business Naming In Jambi City - Muhammad Muslim Nasution; Julisah Izar; Dharma Yunita Siregar; Rizki Ananda; Anggi Triandana; Aprilia Kartika Putri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aimed to examine the phenomenon of multilingual naming in food and beverage businesses in Jambi City, including identifying word types and the reasons behind their name choices. The research method used  a qualitative descriptive approach focused on the presentation and in-depth interpretation of linguistic data. Data collection techniques were conducted through direct field observations to document business signage and in-depth interviews with business owners to explore naming motivations. Data analysis techniques were applied by classifying language use based on the type of meaning and function of the linguistic landscape, which were then interpreted to identify sociolinguistic trends in society. The results show that a number of culinary businesses in Jambi City extensively use multilingual naming, both entirely and in a hybrid manner. Some examples of naming found include Brownmix, Kafaaf, D'Box, D'BestO, Casa de Alicia, Haus Tea, and Love. These findings indicate that multilingual use has two main functions: informative and symbolic. The informative function is reflected in the use of foreign languages ​​to concisely describe product types or business images. Meanwhile, the symbolic function is seen in the efforts of business owners to build a modern, prestigious, and globally oriented identity to increase business competitiveness in the public space of Jambi.